Extremum seeking for dynamic maps using Lie brackets and singular perturbations. (September 2017) - Dürr, Hans-Bernd; Krstić, Miroslav; Scheinker, Alexander; Ebenbauer, Christian
Abstract: We introduce a framework for the analysis of extremum seeking systems for dynamic maps based on Lie bracket approximations and singular perturbation theory. Using the introduced framework, we provide an extremum seeking regulator for a unicycle and prove its stability properties.